(3eNJUQ aj GdJQZjH hGdJQgjHs
(3ChdgG (B:s
(3Chd GdehLhO hUM Yf QShd Gddg Udj Gddg Ydjg hSde hGddg aj Yhf GdYHO eG cGf GdYHO aj Yhf CNjI aQCjJ EPG LejY eNJUQkG ef GdGMGOjK GdUMjMI LGeYkG ddJQZjH hGdJQgjH s
(3BNQgG (B:s
(3bdfG MQeI LdjdI GHf GdQVGY KGHJI HGdMOjK GdeTghQ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs